Measurement of the argon-gas-induced broadening and line shifting of the barium Rydberg level 6s24d 1^D2 by two-photon resonant nondegenerate four-wave mixing - 孙江 熊志强 孙娟 王颖 苏红新 (中国物理B：英文版, 2012)
We apply two-photon resonant nondegenerate four-wave mixing with a resonant intermediate state to the obser-vation of the broadening and shifting of the barium Rydberg level 6s24d 1^D2 by collision with argon. The collision broadening and shifting cross sections are measured. This technique is purely optical, and can investigate the pressure dependence of the transverse relaxation rate-P21 between the Rydberg state and an intermediate state, as well as the transverse relaxation rate F20 between the Rydberg state and the ground state.